Obtaining The Relation Between The Courses By Using Data Mining Application - (:unkn) unknown (DRUNPP-SARAJEVO, 2012)
The amount of data kept every area increases continually in our day. From these data by being carried out data mining techniques, meaningful, precious knowledge which is unknown before is desired to be obtained. Because of this reason, data mining comes in the first line in the process of information exploration on databases. From these data in hand, data mining is extracting potentially handy information which is not so clear, unknown before and up closed [I]. Data mining is not a solution itself at this point, instead it is a tool which supports decision making process and which tries to ensure required knowledge in order to reach the solution of the problem. In data mining techniques, association rules are one of the most preferred techniques. Apriori algorithm is the most used one in these association rules. In this concept, school automation software has been prepared in Microsoft VB.Net programming concept. With this prepared software, by being carried out apriori algorithm upon the data of students of Istanbul Eyup I.M.K.B. Vocational Commerce High School, the rules have been produced and from the results obtained the relation between the courses that the students failed have been revealed. Key words: